A comparative study of amino acid, mineral and vitamin profiles of milk from Turkish Saanen, Hair and Maltese goat breeds throughout lactation. (29th June 2021) - Günay, Emine; Güneşer, Onur; Karagül Yüceer, Yonca
Abstract : This study aimed to evaluate the changes in nutritional compounds such as amino acids, minerals, and vitamins in the milk of Turkish Saanen, Hair and Maltese goat breeds. The Turkish Saanen goat breed had lower dry matter, fat, nitrogen, and vitamins A, E and B2 than Maltese and Hair goat breeds throughout lactation period. High levels of proline, leucine, glutamic acid, and glutamine were found in all breeds. Except for tyrosine, all other amino acids were higher in Hair goat milk than those in other breed milk. The calcium content of the samples ranged from 1164.79 to 1214.16 mg/L.